RISKS AND BENEFITS OF BOXING TRAINING - A LITERATURE REVIEW - Damian Dolata,; Hubert Kostka,; Jeremy Spula,; Aleksandra Maria Krzywoń,; Adrian Zagórski,; Jadwiga Kleinrok,; Anna Bereta-Kostaś,; Rafał Kuśmider,; Małgorzata Leśnik,; Patrycja Wierzbowska, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Boxing, despite significant advancements in protective measures, remains a sport with a high risk of injury. Regular exposure of athletes to powerful blows, especially to the head, poses a serious health threat, both in the short and long term. This study aimed to analyze the most common injuries and complications associated with boxing and the potential benefits derived from training.A brief description of the state of knowledge: The most frequent injuries in boxing affect the head and upper limbs. Neurological injuries, including concussions and their accumulation, can lead to chronic conditions such as chronic traumatic encephalopathy (CTE). Changes in brain activity observed in EEG confirm the impact of trauma on brain function. Injuries to the limbs mainly include fractures and overuse injuries of the hand and wrist joints. An additional threat is the spread of infectious diseases resulting from intense physical contact and weakened immunity. Despite the risks, boxing training promotes improvements in coordination, strength and stress reduction, so it is used in the therapy of mental health disorders.Conclusions: Boxing carries a significant risk of injury; however, with appropriate protective measures and conscious training, it is possible to minimize its adverse effects. The sport can simultaneously bring substantial benefits to physical and mental health, provided that a rational approach to load and recovery is maintained.